Synthesis, electrochemistry, spectroelectrochemistry, and electrochromism of metallophthalocyanines substituted with four (2,4,5-trimethylphenyl)ethynyl groups - BUDAK, ÖZLEM; KOCA, ATIF (My University, 2022)
The synthesis of the novel phthalonitrile containing (2,4,5-trimethylphenyl)ethynyl moieties was performed using the palladium-catalyzed Sonogashira crosslinking methodology. Cobalt phthalocyanine was obtained with the cyclotetramerization reaction of this dinitrile derivative, while the synthesis of zinc and manganese phthalocyanines was reported by the Sonogashira coupling reaction of the appropriate iodo phthalocyanines. Voltammetric and electrochromic analyses were applied to determine the possible applications of these complexes in different electrochemical/display technologies. The rich redox responses of the complexes had a good influence on the spectroelectrochemical characters of them. Electrochromic measurements of the complexes indicated fast, and reversible color changes with reasonable optical contrasts.
Keywords: Kimya; Analitik Kimya; Fizikokimya; Elektrokimya; Temel Bilimler; Chemistry; Analytical Chemistry; Physical Chemistry; Electrochemistry; Natural Sciences; KİMYA, ANALİTİK; Temel Bilimler (SCI); ELEKTROKİMYA; CHEMISTRY, ANALYTICAL; CHEMISTRY; Natural Sciences (SCI); ELECTROCHEMISTRY; Filtration and Separation; Chemistry (miscellaneous); General Chemistry; Physical Sciences; Electrochromism; Metallophthalocyanine; Sonogashira cross-coupling reaction; Spectroelectrochemistry; PHTHALOCYANINE COMPLEXES; PHOTOPHYSICAL PROPERTIES; PERIPHERAL POSITIONS; METAL-FREE; COBALT; MANGANESE; ELECTROPOLYMERIZATION; ZINC(II); ZN(II); Electrochemistry; Electrochromism; Metallophthalocyanine; Sonogashira cross-coupling reaction; Spectroelectrochemistry